Ticari satımda satıcının temerrüdünün sonuçları ve özellikle müspet zarar - Akıncı, Bekir (My University, 2011)
cari satım, ticari satış, temerrüt, satıcının temerrüdü, kesin vade, müsbet zarar, müspet zarar, mübadele teorisi, fark teorisi, fiili zarar, yoksun kalınan kâr, yenilik doğuran haklar, somut metot, soyut metot.

Kesin vadeli ticari satımlarda satıcının temerrüdüne Borçlar Kanununun 187’inci maddesinde birtakım özel sonuçlar bağlanmıştır. Bu sonuçların birisi de satıcının temerrüdü halinde alıcının müspet zarar talep edeceği karinesidir. Bu çalışmada da ticari satımda satıcının temerrüdünün sonuçları ve müspet zarar kavramı ele alınmıştır. Tezimizin ilk bölümünde Borçlar Kanunu madde 187 anlamında “ticari satım sözleşmesi” kavramı, vade türleri ve her bir vadeye bağlanan sonuçlar ve son olarak kesin vadeli ticari satımda satıcının temerrüdü halinde söz konusu olan karineler incelenmiştir. İkinci bölümde ise, müspet zarar kavramına yönelik bir genel bakış ve açıklamalardan sonra, mübadele ve fark teorileri, müspet zarar talep etme şartları, seçim hakkının kullanımı üzerine ortaya çıkan sorunlar ve son olarak alıcının müspet zararının hesaplanmasından bahsedilmiştir. Commercial sale, seller’s default, redemption date, time is of the essence, exchange theory, distinction theory, creative rights. ABSTRACT The Turkish law-maker has concluded particular legal consequences for the results of seller’s default on commercial sales. One of these consequences is the presumption that at the end of the due date, the buyer has right to sue the seller for his expectation interest, which is a component of positive detriment, without informing seller before. Within the scope of this discourse we analysed the results of the default of seller on commercial sales in addition to indemnification of positive detriment in Turkish law. On the first chapter of the discourse we analysed the definition of “commercial sale agreement” within the meaning of Turkish Obligations Law article 187. In addition, variations of redemption date, the presumptions concluded to the results of seller seller’s default on commercials sales are also examined on the first chapter. On the second chapter, after an overview to the positive interest in Turkish law, we set forth the meaning of the exchange and distinction theories, mentioned of the conditions to claim positive interest and discussed the problems arising from the claim of positive detriment indemnification. Eventually at the end of the discourse and second chapter, we mentioned of the calculation of the buyers detriment.
Keywords: Hukuk; Özel Hukuk